Let-7i-5p represses brite adipocyte function in mice and humans - Giroud, Maude; Scheideler, Marcel (Scientific reports, 2016)
In response to cold or β3-adrenoreceptor stimulation brown adipose tissue (BAT) promotes non-shivering thermogenesis, leading to energy dissipation. BAT has long been thought to be absent or scarce in adult humans. The recent discovery of thermogenic brite/beige adipocytes has opened the way to development of novel innovative strategies to combat overweight/obesity and associated diseases. Thus it is of great interest to identify regulatory factors that govern the brite adipogenic program. Here, we carried out global microRNA (miRNA) expression profiling on human adipocytes to identify miRNAs that are regulated upon the conversion from white to brite adipocytes. Among the miRNAs that were differentially expressed, we found that Let-7i-5p was down regulated in brite adipocytes. A detailed analysis of the Let-7i-5p levels showed an inverse expression of UCP1 in murine and human brite adipocytes both in vivo and in vitro. Functional studies with Let-7i-5p mimic in human brite adipocytes in vitro revealed a decrease in the expression of UCP1 and in the oxygen consumption rate. Moreover, the Let-7i-5p mimic when injected into murine sub-cutaneous white adipose tissue inhibited partially β3-adrenergic activation of the browning process. These results suggest that the miRNAs Let-7i-5p participates in the recruitment and the function of brite adipocytes.